The Implementation of Earmarking Tax Policy on Cigarette Tax in West Java Province - Maisarah Putriyandri Atsani; Murwendah Murwendah (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2019)
In an eﬀort to control cigarette consumption in Indonesia, one of the policies used by the government is the earmarking tax policy on cigarette tax. In fact, the prevalence of smoking in Indonesia continues to increase even though the government has imposed various state levies. The purpose of this study is to analyze the implementation of earmarking tax policy on cigarette tax in West Java Province, as one of the regions receiving the largest cigarette tax allocation in Indonesia. This research uses qualitative approach with data collection techniques of literature and in-depth interviews. The results show that the earmarking tax policy on cigarette tax has not been able to reduce the prevalence of smoking since the cigarette tax in the region has not been utilized as per its designation. The function of control of earmarking tax policy on cigarette tax is limited to controlling budgeting aspect; yet, there is no control function related to cigarette tax income to be used according to its purpose (earmarking). Other factors are the cheap price of cigarettes sustained by people’s increasing revenue, massive tobacco advertising, and fervent smoking culture in the community. A partial policy that only relies on state levies is perceived as insuﬃcient to control cigarette consumption, particularly without coordination among stakeholder in central and local governments. In fact, cigarette tax revenue has been budgeted for public health services in West Java Province; nevertheless, its implementation in the field has not been fully utilized for public health services.